Short-Term Daily Consumption of Provitamin A Carotenoid–Biofortified Maize Has Limited Impact on Breast Milk Retinol Concentrations in Zambian Women Enrolled in a Randomized Controlled Feeding Trial. Issue 9 (27th July 2016) - Palmer, Amanda C; Chileshe, Justin; Hall, Andrew G; Barffour, Maxwell A; Molobeka, Ngosa; West, Keith P; Haskell, Marjorie J
Abstract: Background: Provitamin A carotenoid–biofortified maize is a conventionally bred staple crop designed to help prevent vitamin A deficiency. Lactating women are a potential target group, because regularly eating biofortified maize may increase vitamin A in breast milk—a critical source of vitamin A for breastfeeding infants. Objective: We assessed whether daily consumption of biofortified orange maize would increase the retinol concentration in the breast milk of Zambian women. Methods: Lactating women ( n = 149) were randomly assigned to receive orange maize delivering 600 μg retinol equivalents (REs)/d as carotenoid plus placebo (OM), low-carotenoid white maize plus 600 μg REs/d as retinyl palmitate (VA), or white maize plus placebo (WM). Boiled maize (287 g dry weight/d) was served as 2 meals/d, 6 d/wk for 3 wk. We measured initial and final breast milk plasma retinol and β-carotene concentrations, and plasma inflammatory protein concentrations. Results: Groups were comparable at enrollment, with an overall geometric mean milk retinol concentration of 0.95 μmol/L (95% CI: 0.86, 1.05 μmol/L); 56% of samples had milk retinol <1.05 μmol/L. Median capsule and maize intake was 97% and 258 g dry weight/d, respectively. Final milk β-carotene did not vary across groups ( P = 0.76). Geometric mean (95% CI) milk retinol concentration tended to be higher in the OM [1.15 μmol/L (0.96, 1.39 μmol/L)] and VA [1.17 μmol/L (0.99, 1.38 μmol/L)] groups than in the WM group [0.91 μmol/L (0.72, 1.14 μmol/L); P = 0.13], and the proportion of women with milk retinol <1.05 μmol/L was 52.1%, 42.9%, and 36.7% in the WM, OM, and VA groups, respectively ( P -trend = 0.16). Conclusions: Daily biofortified maize consumption did not increase mean milk retinol concentration in lactating Zambian women; however, there was a plausible downward trend in the risk of low milk retinol across intervention groups. This trial was registered at clinicaltrials.gov as NCT01922713.